Standardization and Investigation of Internal Consistency, Reliability, and Criterion Validity of the Fourth Version of the Millon Test (MCMI-IV) - Bazmara, Davoud; Kamkari, Kambiz; Salehi, Mahdieh; Mardani Rad, Mojgan (Journal of Assessment and Research in Applied Counseling (JARAC), 2023)
Objective: The aim of this research was to standardize and investigate the internal consistency, reliability, and criterion validity of the fourth version of the Millon Test (MMCI-IV). Materials and Methods: This study employed an analytical-cross-sectional approach, considering the nature of standardization. The current method focused on the current state and situation, involving both descriptive and correlational methods. The study population consisted of all individuals who referred to counseling centers or clinics in Tehran from June 2022 to September 2022, were at least 18 years old, had a minimum of five years of education, and sought initial treatment or were referred to these centers. In this study, 500 individuals were selected from the population using purposive sampling. The measurement tools included MMCI-IV and the revised form of the Minnesota Multiphasic Personality Inventory-2 (MMPI-2RF). Statistical analysis was performed using Cronbach’s alpha, split-half method, test-retest reliability, Pearson correlation coefficient, and SPSS-26 statistical software. Findings: Cronbach’s alpha and internal consistency, assessed using the split-half method with Spearman-Brown correction, indicated acceptable coefficients for all scales and subscales of this test at a 95% confidence level (p < 0.05). Additionally, the reliability results of this test, assessed using the split-half method, showed significant coefficients at a 95% confidence level, indicating its suitability for reliability (p < 0.05). However, the criterion validity (concurrent validity) of this test with the MMPI-2RF was not confirmed in any of its scales as the correlation coefficient was not significant at a 95% confidence level (p > 0.05). Conclusion: It can be concluded that the standardized fourth version of the Millon Test demonstrates good internal consistency and reliability. However, it does not show concurrent validity with the MMPI-2RF. Therefore, caution should be exercised when using this test as a substitute for the MMPI-2RF.